2021
DOI: 10.1101/2021.07.30.454523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mechanism of MinD stability modulation by MinE in Min protein dynamics

Abstract: The patterns formed both in vivo and in vitro by the Min protein system have attracted much interest because of the complexity of their dynamic interactions given the apparent simplicity of the component parts. Despite both the experimental and theoretical attention paid to this system, the details of the biochemical interactions of MinD and MinE, the proteins responsible for the patterning, are still unclear. For example, no model consistent with the known biochemistry has yet accounted for the observed dual … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…The dynamics in the bulk are coupled to those on the surface through a boundary condition accounting for particle conservation: the flux of particles leaving and entering the cytosol is balanced by the rates of membrane binding and unbinding. Modeling details, including cooperative binding (Loose et al , 2008), further biochemical reactions (Meinhardt & Boer, 2001; Loose et al , 2011; Park et al , 2011; Ayed et al , 2017; preprint: Carlquist & Cytrynbaum, 2021), protein polymerization (Drew et al , 2005; Cytrynbaum & Marshall, 2007), interactions with particular lipids localized at the cell poles (Renner & Weibel, 2012), and advective cytoplasmic flows (Vecchiarelli et al , 2014; Meindlhumer et al , 2023), have been extensively studied and are proposed to play important roles in regulating Min patterns (Vecchiarelli et al , 2016; Wettmann & Kruse, 2018; Ramm et al , 2019; Takada et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics in the bulk are coupled to those on the surface through a boundary condition accounting for particle conservation: the flux of particles leaving and entering the cytosol is balanced by the rates of membrane binding and unbinding. Modeling details, including cooperative binding (Loose et al , 2008), further biochemical reactions (Meinhardt & Boer, 2001; Loose et al , 2011; Park et al , 2011; Ayed et al , 2017; preprint: Carlquist & Cytrynbaum, 2021), protein polymerization (Drew et al , 2005; Cytrynbaum & Marshall, 2007), interactions with particular lipids localized at the cell poles (Renner & Weibel, 2012), and advective cytoplasmic flows (Vecchiarelli et al , 2014; Meindlhumer et al , 2023), have been extensively studied and are proposed to play important roles in regulating Min patterns (Vecchiarelli et al , 2016; Wettmann & Kruse, 2018; Ramm et al , 2019; Takada et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Different groups have shown that the geometry of the cell may play a crucial role in the robust selection of standing wave patterns (Schweizer et al , 2012; Zieske & Schwille, 2013, 2014; Wu et al , 2015). Although the exact mechanism behind the emergence of patterns in different geometries is still under debate (Park et al , 2011; Halatek & Frey, 2012; Halatek et al , 2018; Wettmann & Kruse, 2018; Ramm et al , 2019; preprint: Carlquist & Cytrynbaum, 2021; Takada et al , 2022), protein depletion has been suggested to play an important role in the formation of standing waves (Vecchiarelli et al , 2016), and Brauns et al (2021) propose that this arises due to the narrow geometry of the cells. The boundary condition for the cytosolic concentrations enforces protein conservation.…”
Section: Introductionmentioning
confidence: 99%